Ekstraksi, Karakterisasi, dan Klasifikasi Senyawa Aromatik Jahe (Zingiber Officinale) melalui Metode Enfleurasi Dan Maserasi - Aluna Monalaika Izzati; Ine Pebriyanti (PT. Pubsains Nur Cendekia, 2026)
This study investigates the extraction, characterization, and aromatic classification of ginger (Zingiber officinale) using enfleurage and maceration techniques. Enfleurage was employed as a mild, non-thermal method to preserve thermolabile volatile compounds, while ethanolic maceration was used to obtain aromatic tincture. The resulting extracts were evaluated through organoleptic analysis, physicochemical characterization (pH and density), and aromatic note classification based on volatility and persistence. The results indicate that petrolatum-based enfleurage successfully captured volatile aromatic fractions with dominant top-note characteristics, whereas maceration produced a tincture with stable physicochemical properties and strong initial aroma intensity. These findings demonstrate that method selection significantly influences aroma profile, stability, and applicability in cosmetic and perfumery formulations.